1996
DOI: 10.1007/bf00329704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nutrition and egg provisioning on parameters of larval hatch, survival and dispersal in the gypsy moth, Lymantria dispar L.

Abstract: North American gypsy moths disperse as newly hatched larvae on wind currents in a behavior called ballooning. Because ballooning occurs before neonates begin to feed, resources used in dispersal are limited to those carried over from the egg. We show that nutritional experience of the maternal parent can influence the tendency of offspring to disperse, and that resource provisioning of eggs by the maternal parent affects the duration of the window for disperal. Offspring of females from defoliated sites had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 20 publications
5
73
2
Order By: Relevance
“…Furthermore, the environment may be sampled at different times, both within the lifetime of the individual and in some cases, the environment of past generations may be transmitted through maternal effects (e.g. Dixon, 1985;Diss et al, 1996;Massot et al, 2002;see Ims, 1990 for a counter example). How the organism integrates the information from different environmental cues and thereby reaches its decision has largely been overlooked (Ronce et al, 2001 ;Massot et al, 2002).…”
Section: (4 ) Integration Of Environmental Factors In Decision Makingmentioning
confidence: 99%
“…Furthermore, the environment may be sampled at different times, both within the lifetime of the individual and in some cases, the environment of past generations may be transmitted through maternal effects (e.g. Dixon, 1985;Diss et al, 1996;Massot et al, 2002;see Ims, 1990 for a counter example). How the organism integrates the information from different environmental cues and thereby reaches its decision has largely been overlooked (Ronce et al, 2001 ;Massot et al, 2002).…”
Section: (4 ) Integration Of Environmental Factors In Decision Makingmentioning
confidence: 99%
“…Dispersal occurs before feeding and therefore depends on the resources in the egg acquired by the mother during her own larval stage (Diss et al 1996). Leonard (1970aLeonard ( , 1970b found that smaller eggs from dense populations produce larvae with a longer pre-feeding period and a higher activity level, even in the presence of suitable food, and suggested that these larvae have a greater tendency to disperse.…”
Section: Gypsy Mothmentioning
confidence: 99%
“…Leonard (1970aLeonard ( , 1970b found that smaller eggs from dense populations produce larvae with a longer pre-feeding period and a higher activity level, even in the presence of suitable food, and suggested that these larvae have a greater tendency to disperse. However, more recent work has failed to replicate this result (Diss et al 1996) and suggests that the most important factors in dispersalassociated mortality are host-plant synchrony and weather during dispersal, not maternal quality or population density (Erelli and Elkinton 2000).…”
Section: Gypsy Mothmentioning
confidence: 99%
“…Large eggs generally have fitness advantages in Lepidoptera (Braby, 1994;Sinervo, 1993;Stearns, 1992), as they lead to greater over-winter survival [Choristoneura fumiferana (Carisey and Bauce, 2002)], higher probability of hatching [M. disstria (McCowan, 1952)] and larger, more active, caterpillars [Malacosoma pluviale (Wellington, 1965); Lymantria dispar (Diss et al, 1996)] with longer resistance to starvation [Lobesia botrana (Torres-Villa and Rodriguez-Molina, 2002)] in the next generation. In the forest tent caterpillar, larger eggs are thought to confer an advantage in cold climates, where hatchlings sometimes emerge into harsh conditions where food is not immediately available (Cooke and Roland, 2003;Parry et al, 2001).…”
Section: N Colasurdo Y Gélinas and E Desplandmentioning
confidence: 99%